Novel molecules and target genes for vegetative heat tolerance in wheat. Issue 6 (26th December 2022) - Rose, Teresa; Wilkinson, Mark; Lowe, Claudia; Xu, Jiemeng; Hughes, David; Hassall, Kirsty L.; Hassani‐Pak, Keywan; Amberkar, Sandeep; Noleto‐Dias, Clarice; Ward, Jane; Heuer, Sigrid
Abstract: To prevent yield losses caused by climate change, it is important to identify naturally tolerant genotypes with traits and related pathways that can be targeted for crop improvement. Here we report on the characterization of contrasting vegetative heat tolerance in two UK bread wheat varieties. Under chronic heat stress, the heat‐tolerant cultivar Cadenza produced an excessive number of tillers which translated into more spikes and higher grain yield compared to heat‐sensitive Paragon. RNAseq and metabolomics analyses revealed that over 5000 genotype‐specific genes were differentially expressed, including photosynthesis‐related genes, which might explain the observed ability of Cadenza to maintain photosynthetic rate under heat stress. Around 400 genes showed a similar heat‐response in both genotypes. Only 71 genes showed a genotype × temperature interaction. As well as known heat‐responsive genes such as heat shock proteins (HSPs), several genes that have not been previously linked to the heat response, particularly in wheat, have been identified, including dehydrins, ankyrin‐repeat protein‐encoding genes, and lipases. Contrary to primary metabolites, secondary metabolites showed a highly differentiated heat response and genotypic differences. These included benzoxazinoid (DIBOA, DIMBOA), and phenylpropanoids and flavonoids with known radical scavenging capacity, which was assessed via the DPPH assay. The most highly heat‐induced metabolite was (glycosylated) propanediol, which is widely used in industry as an anti‐freeze. To our knowledge, this is the first report on its response to stress in plants. The identified metabolites and candidate genes provide novel targets for the development of heat‐tolerant wheat. Abstract : Chronic heat stress induces distinct physiological, metabolomic, and transcriptomic changes in a heat‐tolerant Triticum aestivum cultivar, Cadenza, compared to a susceptible cultivar, Paragon. Previously uncharacterized metabolites and genes are differentially regulated in the heat‐tolerant cultivar, providing potential for future crop heat tolerance improvement.